2020
DOI: 10.1038/s41467-020-17639-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial polyphosphates interfere with the innate host defense to infection

Abstract: Polyphosphates are linear polymers and ubiquitous metabolites. Bacterial polyphosphates are long chains of hundreds of phosphate units. Here, we report that mouse survival of peritoneal Escherichia coli sepsis is compromised by long-chain polyphosphates, and improves with bacterial polyphosphatekinase deficiency or neutralization using recombinant exopolyphosphatase. Polyphosphate activities are chain-length dependent, impair pathogen clearance, antagonize phagocyte recruitment, diminish phagocytosis and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 68 publications
1
93
1
Order By: Relevance
“…It has already been demonstrated that polyP shows biological effects in a chain length-dependent manner (Angelova et al, 2016). Indeed, bacterial long-chain polyP has been shown to potentiate pathogenicity by inhibiting phagosome maturation (Roewe et al, 2020) and interfering with macrophage function (Rijal et al, 2020). Therefore, it is suggested that the response of polyP to inflammation will be different depending on the dose and degree of polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been demonstrated that polyP shows biological effects in a chain length-dependent manner (Angelova et al, 2016). Indeed, bacterial long-chain polyP has been shown to potentiate pathogenicity by inhibiting phagosome maturation (Roewe et al, 2020) and interfering with macrophage function (Rijal et al, 2020). Therefore, it is suggested that the response of polyP to inflammation will be different depending on the dose and degree of polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…Early and rapid detection is key for lowering the basic reproduction number of infected individuals. Nanoparticles can be engineered as biosensors for the detection of biomarkers, including nucleic acids (DNA, RNA), specific antigens (proteins, enzymes), or antibodies in order to rapidly and accurately detect SARS-CoV-2 (143,149,181,182). Recent advancements in nanotechnology have allowed for the release of a SARS-CoV-2 detection platform that uses graphene conjugated to an anti-spike antibody.…”
Section: Nanoparticles In Diagnosticsmentioning
confidence: 99%
“…Manipulation of polyP levels has been proposed as a therapeutic for ulcerative colitis, [ 75 ] bacterial [ 64 ] and viral infection, [ 68,76 ] and wound healing. [ 77 ] Given the breadth of processes impacted by polyP, we are likely to see additional clinical applications in the near future.…”
Section: Promises and Challengesmentioning
confidence: 99%
“…Finally, recent work by Roewe et al presents data suggesting that macrophages can internalize bacterial long-chain polyP and that this inhibits the immune response. [64] Here again, it would be interesting to test if this results in polyphosphorylation of mammalian proteins involved in infection control. It is also tempting to speculate that such polyphosphorylations might be prevented by treatment with mesalamine, a drug used to treat inflammatory bowel disease that serves as an inhibitor of bacterial PPK enzymes.…”
Section: The Highs and The Lows-linking Polyp Concentration To Lysine Polyphosphorylationmentioning
confidence: 99%